Where to from Here? Women Remain Absent from Senior Academic Positions at Aotearoa New Zealand's Universities - Leilani Walker; Isabelle Sin; Cate Macinnis-Ng; Kate Hannah; Tara McAllister (MDPI AG, 2020)
In light of policies and programs designed to address the domination of academic positions by male, frequently white individuals, we review the participation of women, one of multiple minority identities within the academy, in Aotearoa New Zealand's academic workforce using employment data from eight universities from 2002-2017. While the number of women employed continues to improve, the rate has slowed in recent years and senior roles remain heavily dominated by men. Women were more likely to be employed at lower levels of seniority, to advance to seniority more slowly than male colleagues, and were more likely to be employed part-time. We call for active strategies to address the cultural and structural bias in universities that favour the hiring and promotion of men to improve workforce diversity at all levels of seniority.